Pengembangan Unit Usaha Pembuatan Sanggan pada Bahan Usaha Milik Nagari Tunas Mekar Simpuruik, Kecamatan Sungai Tarab, Kabupaten Tanah Datar, Sumatera Barat - Rita Rahayu; Fery Adrianus; Rayna Kartika; Annisa Rahman (Warta Pengabdian Andalas, 2022)
The activity aimed to assist Village-Owned Enterprises in Nagari Simpuruik, Sungai Tarab District, Tanah Datar Regency, West Sumatra. It has been developing business units based on village potential as it is known that today Nagari Simpuruik is famous for its "ketupat", i.e. rice cake boiled in a rhombus-shaped packet of plaited young coconut leaves. It is made of coconut leaves and produces coconut sticks as waste. Coconut sticks can be used and processed into value-added products. Seeing this potential, a community service team from the Faculty of Economics and Business of Andalas University formed a business unit by involving the Nagari Simpuruik community under the auspices of a Nagari-Owned Enterprise to produce products made from the coconut sticks known as "Sanggan". These activities consisted of surveys, Focus Group Discussions, and training. This activity certainly involves the people of Nagari Simpuruik, and it is hoped that this activity will encourage the improvement of the community's economy. The result of this activity is the form of increasing the community's ability to process waste into value-added products.